Using graph embeddings for Wikipedia link prediction - Shaptala, Roman Vitaliyovych; Kyselev, Gennadiy Dmytrovych (НТУ "ХПІ", 2019)
Link prediction is an important area of study in network analysis and graph theory which tries to answer the question of whether two nodes in the graph might have an association in the future. Nowadays, graphs are ubiquitously present in our lives (social networks, circuits, roads etc.), which is why the problem is crucial to the development of intelligent applications. In the past, there have been proposed methods of solving link prediction problem through algebraic formulations and heuristics, however, their expressive power and transferability fell short. Recently, graph embedding methods have risen to popularity because of their effectiveness and the ability to transfer knowledge between tasks. Inspired by the famous in machine learning and natural language processing research Word2Vec approach, these methods try to learn a distributed vector representation, called an embedding, of graph nodes. After that a binary classifier given a pair of embeddings predicts the probability of the existence of a link between the encoded nodes. In this paper, we review several graph embedding approaches for the problem of Wikipedia link prediction, namely Wikipedia2vec, Role2vec, AttentionWalk and Walkets. Wikipedia link prediction tries to find pages that should be interlinked due to some semantic relation. We evaluate prediction accuracy on a hold-out set of links and show which one proves to be better at mining associations between Wikipedia concepts. The results include qualitative (principal component analysis dimensionality reduction and visualization) and quantitative (accuracy) differences between the proposed methods. As a part of the conclusion, further research questions are provided, including new embedding architectures and the creation of a graph embedding algorithms benchmark.

Прогнозування зв'язків є важливою областю дослідження в аналізі мереж та теорії графів, яка намагається відповісти на питання, чи можуть два вузли у графі в майбутньому мати зв'язок. На сьогоднішній день графи повсюдно присутні у нашому житті (соціальні мережі, електротехніка, дороги і т. д.), тому проблема має вирішальне значення для розвитку інтелектуальних додатків. У минулому були запропоновані методи вирішення задачі прогнозування зв'язків за допомогою алгебраїчних формулювань і евристик, однак їхня виразність і переносимість не були задовільними. Останнім часом методи побудови векторних представлень зросли у популярності через їх ефективність і здатність передавати знання між завданнями. Натхненний знаменитим в машинному навчанні та обробці природних мов дослідницьким підходом Word2Vec, ці методи намагаються вивчити розподілене векторне представлення. Після цього бінарний класифікатор, заданий парою таких векторів, прогнозує ймовірність існування зв'язку між закодованими вузлами. У даній роботі ми розглянемо декілька підходів до вбудовування графіків для проблеми прогнозування зв'язків у Wikipedia, а саме Wikipedia2vec, Role2vec, AttentionWalk та Walkets. Прогнозування посилань у контексті Wikipedia – це знаходження сторінок, які пов'язані через певні смислові відносини. Ми оцінюємо точність прогнозування на відокремленому наборі зв'язків і показуємо, який з методів краще знаходить асоціації між сутностями у Вікіпедії. Отримані результати включають якісні (метод головних компонентів для зменшення розмірності та візуалізації) і кількісні (точність) відмінності між запропонованими методами. У рамках висновку наводяться подальші дослідницькі питання, включаючи нові архітектури побудови векторних представлень та створення загальноприйнятого тесту ефективності таких представлень .
Використання векторних представлень графів для прогнозування зв'язків у Wikipedia
Keywords: Walklets; principle component analysis; network analysis; algorithm; векторні представлення даних; прогноз зв'язків; метод головних компонентів